Using Visual Evoked Potential to Study the Effect of Methotrexate on Retina - M, Chanio; KS, Makhori; N, Kenoki; L, Shinol; N, Arozi (Journal of Ophthalmology and Research, 2019)
Methotrexate is a drug generally used to treat some types of cancer or to control severe psoriasis or rheumatoid arthritis that has not responded to other treatments. Methotrexate belongs to a class of drugs known as antimetabolites. It works by suppressing the immune system. Common side effects of this drug may include fever, chills, tiredness, mouth sores; nausea, upset stomach, dizziness. The aim of this research is to check if this drug has a probable toxic effect on retina. It is a case control study with 16 patients taking Methotrexate for more than one year and 16 healthy population without using the drug. Visual evoked potential (VEP) was recorded, Latency and amplitude of P100 peak was measured in all 32 subjects. Mean and standard deviation were calculated for each group. The mean latencies /SD and amplitudes /SD of VEP, P100 obtained in two groups compared together. There was no statistically significant difference between two groups. Based on the result, we can conclude that visual pathway is not affected in patients taking Methotrexate.